Conceptual Design Of Shielded Metal Arc Welding Workstation: Work Posture And Bead Dimension Consideration - Halim, Isa; Radin Umar, Radin Zaid; Ahmad, Nadiah; Abdul Rahim, Ruslinda; Zakaria, Nurul Farahizzati (Universiti Teknikal Malaysia Melaka (UTeM), 2017)
The aim of this study was to propose a conceptual design of SMAW workstation which considered work postures of welders and weld bead dimensions. This study applied full factorial design of experiment. The independent variables were table height, table surface inclination, and work position whereas the dependent variables were bead height, bead width, and RULA score. Results of analysis of variance showed that the table height, table surface inclination, and work position had an effect on bead width and bead height. This study concluded that the proposed SMAW workstation can offer acceptable bead dimensions when it is designed with adjustable table height, flat table surface (0°), and standing work position. However, the work posture still requires further investigation.